PERLINDUNGAN HUKUM BAGI KONSUMEN MUSLIM TERHADAP PRODUK KOSMETIK YANG MEMILIKI KANDUNGAN NON-HALAL DI INDONESIA - Rahmi Ayunda; Viola Zahra Ananda Kusuma (Maleo Law Journal, 2021)
Assurance of halal products becomes very important when reviewed on an advancement of technology and science that the management of the product uses raw materials that can occur a mixture of composition between halal and not halal either intentionally or unintentionally, because this happens to every community in daily needs. Therefore, the guarantee of halal in every product must exist with halal certification and label, in order to protect consumers from non-halal cosmetic products. Research and writing this article, the author uses legal research with a normative approach by using secondary data is a data obtained from the literature. Majelis Ulama Indonesia or abbreviated MUI is a non-governmental organization in accommodating Islamic scholars, scholars in Indonesia who have the aim to direct and guide and foster all Muslims in Indonesia Keywords: Legal protection, cosmetic product, non-halal